Ex-vitro establishment of Phalaenopsis amabilis seedlings in different substrates = Aclimatização “ex-vitro” de plântulas de Phalaenopsis amabilis em diferentes substratos - Giorgini Augusto Venturieri; Elsa Aurora Mendoza de Arbieto (Acta Scientiarum: Agronomy, 2011)
Eight substrates were evaluated for ex-vitro establishment of Phalaenopsis amabilis seedlings. They were: Fibraflor® (commercial substrate), Turfa Fértil FG2® (commercial substrate), vermiculite, coconut fiber from the pericarp, decomposed pine bark, organic compost, sphagnum and shredded xaxim, in the establishment of seedlings of Phalaenopsis amabilis L., in combination, with and without immersion of the seedlings, after they were removed from the growth flasks, in Manzate 800 at a dosage of 1 g L1. The evaluated parameters were: the sum of the lengths of the two largest leaves, the sum of the lengths of the three largest roots and the percentage of surviving seedlings, evaluated at 190 days after planting. It was observed that there were significant differences between substrates, and sphagnum and shredded xaxim were the best in performance. Theapplication of Manzate 800 showed interaction with substrates, but the isolated effect was not significant. Sphagnum is also an extractive product, but when it is impossible to obtain, an organic compost such as Turfa Fértil FG2® or Fibraflor® can be used, with the necessary application of Manzate 800. Foram avaliados oito substratos na aclimatação “ex-vitro” de mudasde Phalaenopsis amabilis. Eles foram: Fibraflor® (substrato comercial), Turfa Fértil FG2® (substrato comercial), vermiculita, casca de coco dilacerada, casca de pinheiro decomposta, composto orgânico, esfagno e xaxim desfibrado, para a aclimatação de plântulas de Phalaenopsis amabilis L., em combinação com e sem imersão das plântulas, logo após a retirada dos frascos de crescimento, em Manzate 800 na dosagem de 1 g L1. Os parâmetros avaliados foram: soma do comprimento das duas maiores folhas, a soma do comprimento das três maiores raízes e porcentagem de plântulas sobreviventes, avaliados aos 190 dias após o plantio. Observou-se que houve diferenças significativas entre substratos, sendo os de maior desempenho o esfagno e o xaxim desfibrado. A aplicação do Manzate 800 mostrou interação com os substratos, mas o efeito isolado não foi significativo. Na impossibilidade de ser obtido o esfagno, que também é um produto extrativo, poderiam ser usados: o composto orgânico, a Turfa Fértil FG2® ou o Fibraflor®, com a necessária aplicação do Manzate 800.